Business Process Innovations and Business Changes - Zuzana ROSNEROVA (Communications of International Proceedings, 2021)
The current market environment is characterized by turbulent developments, which greatly affect the activities of businesses. Businesses are forced to make changes in order to adapt to changing market conditions. The present shows that in many cases, the basic determinant for the start of business change is the customer and his needs, which are constantly changing and evolving. Businesses make changes to meet customer requirements in order not to lag behind the competition. The development of companies depends on the ability to design such business processes, through which it can implement change and become competitive. The aim of the article is to identify the difference between the functional and process approach to management and to determine the ways in which it is possible to make changes in process management, i.e. business process innovation. In this article I work with the hypothesis that changes made only in functional management are insufficient and it is desirable for companies to implement changes that will relate to process management and will therefore interfere with business processes based on continuous improvement of business processes or radical approach to implementation business changes in processes. The hypothesis proved to be true, as the development of competitiveness in the market depends on the innovation of business processes.
Keywords: Business Changes; Process Control; Functional Control; Reengineering; Metamorphing; CMMI